Biomedical Engineering Systems and Technologies Third International Joint Conference, BIOSTEC 2010, Valencia, Spain, January 20-23, 2010, Revised Selected Papers - Fred, Ana; Filipe, Joaquim; Gamboa, Hugo (Springer eBooks., 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the Third International Joint Conference on Biomedical Engineering Systems and Technologies, BIOSTEC 2010, held in Valencia, Spain, in January 2010. The 30 revised full papers presented together with 1 invited lecture were carefully reviewed and selected from a total of 410 submissions in two rounds of reviewing and improvement. The papers cover a wide range of topics and are organized in four general topical sections on healthinf, biodevices, biosignals, and bioinformatics.